2015
DOI: 10.1155/2015/971506
|View full text |Cite
|
Sign up to set email alerts
|

Timing of First Antenatal Care Attendance and Associated Factors among Pregnant Women in Arba Minch Town and Arba Minch District, Gamo Gofa Zone, South Ethiopia

Abstract: Objective. To assess the timing of first antenatal care attendance and associated factors among pregnant women in Arba Minch Town and Arba Minch District, south Ethiopia. Method. Facility based cross-sectional study employing both quantitative and qualitative methods was conducted from February to March, 2014, in Arba Minch Town and Arba Minch District. Data were collected from 409 pregnant women attending antenatal care clinics in nine public health facilities using systematic random sampling. Analysis was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
102
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 29 publications
42
102
8
Order By: Relevance
“…Being aged 14–34 years, being in the fourth or fifth wealth quintile and home visits by VHTS in the intervention area predicted early ANC attendance in this study. The association between an inability to attend ANC early and belonging to the poorest (first) wealth quintile is probably related to the fact that financial barriers are one of the factors that hinder early utilization of ANC services [3537]. The VHTs, on the other hand, are likely to have convinced the women to attend ANC early by providing health education about the importance of early ANC attendance [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being aged 14–34 years, being in the fourth or fifth wealth quintile and home visits by VHTS in the intervention area predicted early ANC attendance in this study. The association between an inability to attend ANC early and belonging to the poorest (first) wealth quintile is probably related to the fact that financial barriers are one of the factors that hinder early utilization of ANC services [3537]. The VHTs, on the other hand, are likely to have convinced the women to attend ANC early by providing health education about the importance of early ANC attendance [38].…”
Section: Discussionmentioning
confidence: 99%
“…The VHTs, on the other hand, are likely to have convinced the women to attend ANC early by providing health education about the importance of early ANC attendance [38]. Ignorance about the importance of attending ANC early, and the gestational age at which women should attend their first ANC, is one reason that has been given for delayed attendance at ANC [35,37]. Moreover, work carried out in Uganda has shown that the main reason that many women give for attending ANC is to collect an antenatal card, which they can use during delivery, rather than to check on their own well-being and that of the baby [39].…”
Section: Discussionmentioning
confidence: 99%
“…14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam. 26 Differences in culture or socioeconomic status or health knowledge including awareness on the importance of early booking for ANC or education level among study populations, or differences in time of study or study area whether urban or rural may also be responsible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation